ENGLISH CONVERSATION TRAINING FOR HIGH SCHOOL STUDENTS IN KISARAN - Meikardo Samuel Prayuda; Dolli Rotua Sinaga; Candra Ronitua Gultom (PEDAMAS (PENGABDIAN KEPADA MASYARAKAT), 2023)
This debate focuses on important elements for teaching high school students to improve their English conversational skills. The importance of choosing proper resources, fascinating topics, and acceptable skill levels is highlighted. Role-playing, brainstorming, and group discussions are examples of excellent teaching techniques that promote active engagement and error correction. The engagement of the students demonstrated a high level of interest in rehearsing the discussion. This behaviour encourages the pupils to practice better conversation, which will eventually improve their conversational skills. The main emphasis is on improving speaking talents, boosting confidence, and giving consistent feedback through a variety of techniques. With the help of this community service initiative, teachers and students will be able to have fruitful conversations and share information and creative teaching techniques. The discussion's overall goal is to improve English language learning opportunities and foster creativity in classroom instruction. All of the students are deemed to have more knowledge and confidence in practicing English conversation by the conclusion of this community service.